2013
DOI: 10.2522/ptj.20120065
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Students of the Medical University of Silesia in Poland

Abstract: There was a large group of medical students who, despite being aware of benefits of physical activity, did not meet the recommended level of physical activity. Physical therapist students are well trained and qualified to promote healthy habits and encourage individuals to undertake regular physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 30 publications
4
54
1
3
Order By: Relevance
“…In Italy, the situation was similar, as more than half of the cardiologists surveyed by Temporelli et al [17] showed a normal BMI but high physical activity was observed in only 15.1% of individuals. Moreover, Dąbrowska-Galas et al [18] also confirmed this kind of relationship in medical students from Poland. Despite the fact that the BMI median value of the future physicians was 21.55, only 22% demonstrated a high physical activity index.…”
Section: Body Mass Indexsupporting
confidence: 55%
See 2 more Smart Citations
“…In Italy, the situation was similar, as more than half of the cardiologists surveyed by Temporelli et al [17] showed a normal BMI but high physical activity was observed in only 15.1% of individuals. Moreover, Dąbrowska-Galas et al [18] also confirmed this kind of relationship in medical students from Poland. Despite the fact that the BMI median value of the future physicians was 21.55, only 22% demonstrated a high physical activity index.…”
Section: Body Mass Indexsupporting
confidence: 55%
“…In the research study of El-Giany et al [5], it was also visible that quite many future physicians from Egypt and Saudi Arabia were not interested in sports. In the survey on Polish medicine students, Dąbrowska-Galas et al [18] observed that physical activity was an important part in their everyday lives (82% of the participants), but only 68% confirmed the necessity of doing regular exercise regularly.…”
Section: Lack Of Interest In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the amount of physical activity in university students, as well as students of medical universities and schools, was the subject of several recent studies in South Asia, South Africa, Europe [20,21,22,23,24,25,26,27] and Ukraine [2]. The results show that the downward trend in college students' physical activity deserves more attention.…”
Section: Introductionmentioning
confidence: 94%
“…the issues of physical activity of students both in bio-physiological and cultural terms are more and more commonly undertaken on different continents: asia [8], Europe [9,10], africa [11,12], and in different countries [13,14,15], including medical universities' students [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%